Android-Based Interactive Learning Multimedia: Social Studies Material for Fourth Grade Elementary School Students - Gusti Izhar; Anwar Senen; Kristi Wardani; Dita Salsavira Cahaya Ningrum (Jurnal Ilmiah Sekolah Dasar, 2023)
Today's learning media have yet to facilitate students' involvement in the learning process fully. This study aims to develop and analyze the effectiveness of Android-based interactive learning multimedia on economic activity material and its relationship to various fields of work and social and cultural life in the environment around elementary school students. The development model used is the Borg and Gall model with 10 development steps. The research subjects used 86 students and 4 grade IV elementary school teachers. The trial was conducted twice, and the operational or effectiveness test used a quasi-experimental design with a nonequivalent control-group design. Data was collected using interviews, questionnaires, scales, and tests. The data analysis technique used is qualitative and quantitative using the T-test. The results of this development research show that the developed Android-based interactive learning multimedia meets the eligibility criteria of "very feasible" with a score of 91 from the material expert and a score of 102 from the media expert, through the results of field trials fulfilling the practicality criteria of "very practical". The t-test analysis results show a significant difference in social studies learning outcomes of students who use Android-based interactive multimedia learning. It was concluded that multimedia based on Android is feasible, practical, and effective for fourth-grade elementary school students' social studies learning.